2000
DOI: 10.1116/1.591169
|View full text |Cite
|
Sign up to set email alerts
|

High-performance silicon dioxide etching for less than 0.1-μm-high-aspect contact holes

Abstract: Very uniform and high aspect ratio anisotropy SiO 2 etching process in magnetic neutral loop discharge plasma Study on characterizing fluorocarbon polymer films deposited on an inner surface during high-aspect-ratio contact hole etching using secondary ion mass spectroscopy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 22 publications
4
33
0
Order By: Relevance
“…From this, it can be deduced that CF 3 I generates very low amount of free fluorine. This was later confirmed by S. Samukawa et al [6] where they used CF 3 I in an Ultra-High Frequency plasma and observed a dominant CF 3 + generation.…”
Section: A Plasma Analysissupporting
confidence: 64%
“…From this, it can be deduced that CF 3 I generates very low amount of free fluorine. This was later confirmed by S. Samukawa et al [6] where they used CF 3 I in an Ultra-High Frequency plasma and observed a dominant CF 3 + generation.…”
Section: A Plasma Analysissupporting
confidence: 64%
“…The dominant ion is CF in the CF plasma, but the relative abundance of CF , CF , or CF depends on pressure and magnetic field [7]. Various radicals are present: CF , 1-3, C H F (high-molecular-weight radicals), etc., but the CF radical has been reported as the dominant species in the fluorocarbon plasmas by many authors [8], [9]. The Ar gas dilutes the radical densities.…”
Section: Introductionmentioning
confidence: 98%
“…[11][12][13][14] In order to reduce PFC emissions, many studies have been carried out to identify environmentally benign alternatives to PFCs, including unsaturated fluorocarbons ͑UFCs͒, such as hexafluoropropene ͑C 3 F 6 , CF 2 v CF-CF 3 ͒, hexafluoro-1,3-butadiene ͑C 4 F 6 , CF 2 v CF-CFv CF 2 ͒, octafluorocyclopentene ͑C 5 F 8 ͒, etc., as well as to determine their etching characteristics. [15][16][17] Although there have been many studies of compounds with alternative chemistry to PFCs for potential applications in the fabrication of microelectronics devices, there are few reports on the use of alternative materials in the Bosch process.…”
Section: Introductionmentioning
confidence: 99%